Human Resource Quality at the Gowa Regency Communication and Informatics Office - Pramudita, Putri; Jamaluddin, Jamaluddin; Darwis, Muh. (ASHA Publishing, 2025)
Human Resources (HR) quality reflects how these individuals can make valuable and practical contributions in achieving organizational or societal goals. Evaluate the quality of human resources at DISKOMIFO SP Gowa Regency and factors that support and hinder these qualities. The approach used is qualitative research with a descriptive approach. Data collection techniques include interviews and documentation, while data analysis techniques include data reduction, data presentation, and conclusion drawing and verification. The results of this study show that all indicators used in the research on the quality of human resources at the DISKOMIFO SP Office of Gowa Regency are relatively good. This is evidenced by relatively relevant indicators of knowledge and skills, which are reflected in their performance. Education is classified as good because most employees have a high educational background, which aligns with the Organization's performance needs. The Understanding Indicator is good because employees understand the importance of their work, which is achieved through various organizational initiatives, such as regular training, project participation, coaching, and team collaboration. The ability indicator is classified as good because employees can adapt to changes in work, and employee performance increases. The indicator of work morale is relatively good because each employee has fluency and internal motivation to maintain working time. Planning and organizing indicators are classified as good because, before the implementation of projects or activities, it is ensured that all activities are completed with a clear and organized approach.